Dynamics of the Typhoon Haitang Related High Ozone Episode over Hong Kong - Xiaolin Wei; Ka-se Lam; Chunyan Cao; Hui Li; Jiajia He (Advances in Meteorology)
It has been previously established that photochemical smog occurring in the Pearl River Delta Region (PRD) was associated with stagnant meteorological conditions. However, the photochemical smog (17 July to 20 July 2005) induced by typhoon Haitang was associated with moderate wind speed and nonstagnant meteorological conditions. The dynamic process of this ozone episode was studied using an integrated numerical model, that is, a mesoscale meteorological model and Community Multiscale Air Quality (CMAQ) model. Model performance has been evaluated using both ground-based meteorological and air quality observations. Analysis of simulated wind fields and ozone budget has been performed. This dynamic process is summarized into three physical factors. First, the westerly wind placed Hong Kong directly downwind of the PRD emissions. Second, the convergence of wind flow stimulated a vertical local circulation near the surface layer. This recirculation allowed primary and secondary pollutants to accumulate. Third, the conditions of high air temperature and low humidity resulted in active photochemical reactions. These combined effects resulted in the formation of high ozone in this episode.